Integrasi Nilai Ketauhidan dan Ekopedagogi dalam Kurikulum Madrasah Ibtidaiyah untuk Penguatan Karakter Peduli Lingkungan - Anwar, Saeful; Frida Maulani; Wina Lutfiah; Syadiah, Siti Ima Halimatu; Azizah , Astri Syifa Nur (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study aims to formulate a conceptual framework for integrating the values of monotheism and the eco-pedagogical approach into the curriculum of Madrasah Ibtidaiyah (MI). Monotheism as a spiritual foundation and eco-pedagogy as a participatory approach are considered relevant in addressing the challenges of character education and the global ecological crisis. The method used is a literature review with a qualitative approach, involving analysis of scientific articles, academic books, and educational policy documents related to Islamic character education and environmental awareness. Content analysis techniques were used to identify key concepts, gaps in the literature, and the potential for integration between the two approaches. The analysis revealed that environment education based on monotheistic values can strengthen students' spiritual awareness of ecological responsibility, while the application of eco-pedagogical principles can provide deep contextual learning experiences. The synergy between the two is believed to shape students' character to be not only religious but also caring and taking concrete action towards the environment. However, this study has limitations as it is theoretical and does not include field implementation testing. Further empirical research is highly recommended to test the effectiveness of the proposed curriculum model. This study is expected to contribute conceptually to the development of a holistic and sustainable MI curriculum